Remote Control: Collaborative Scoring and the Question of Authorship - Kmet, Nicholas (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2018)
Perhaps the most interesting – and controversial – aspect of Hans Zimmer’s Remote Control Productions is the collaborative workflow that many of the film scores that pass through the Santa Monica studio are produced under. While Zimmer and business partner Steven Kofsky have taken great pains in interviews to emphasize the independence of composers working at the Santa Monica studio – Kofsky has said that “these composers are independent, have their own businesses, and secure their own movies” – the reality is one of frequent collaboration. The website for the studio’s parent company – a joint venture between Zimmer, Kofsky, and Lorne Balfe – advertises that “clients have access to over a dozen composers and music editors;” composer collaboration is clearly a prime selling point of Zimmer’s business.An important side-effect of this process is that it has often become difficult – if not impossible – for scholars and enthusiasts to determine the authorship of individual cues within scores. It is not uncommon for as many as five composers – including some of the more prominent names at the studio – to be credited as providing additional music or filling other roles in the music department. This article examines the collaborative process practiced at Zimmer’s Remote Control Productions, and how it challenges traditional notions of authorship in relation to the Hollywood film score.